2006
DOI: 10.1111/j.1439-0396.2005.00614.x
|View full text |Cite
|
Sign up to set email alerts
|

Nutritional physiology of neonatal calves*

Abstract: Summary The gastrointestinal tract of neonatal calves is relatively mature but still requires morphological and functional changes. The intake of colostrum with its nutrient and non‐nutrient components exerts marked effects on gastrointestinal development and function. Colostrum intake provides immunoprotection (passive immunity by immunoglobulins) and is essential for survival of neonates of most species. Furthermore, there are important transient as well as long‐lasting systemic effects on the nutritional st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
168
0
11

Year Published

2009
2009
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 161 publications
(184 citation statements)
references
References 109 publications
(182 reference statements)
5
168
0
11
Order By: Relevance
“…MRF (n = 40) and control (n = 22). Graugnard, Samuel, Xiao, Spangler and Brennan (Simmen et al, 1990;Hanson et al, 2001;Blum, 2006;Newburg and Walker, 2007). Our study reported a greater percentage of protein and total solids less fat in the milk of the group supplemented with MRF.…”
Section: Discussionsupporting
confidence: 53%
“…MRF (n = 40) and control (n = 22). Graugnard, Samuel, Xiao, Spangler and Brennan (Simmen et al, 1990;Hanson et al, 2001;Blum, 2006;Newburg and Walker, 2007). Our study reported a greater percentage of protein and total solids less fat in the milk of the group supplemented with MRF.…”
Section: Discussionsupporting
confidence: 53%
“…Colostrum is itself highly nutritious. It is also associated with improved gut maturity (Blum, 2006) and improved health (McGuirk, 2008). Calves moved to a separate rearing unit also had a higher ADG from 1 to 63 days.…”
mentioning
confidence: 93%
“…This pattern is typical for foetal or pre-colostral sera in some animal species. In calves and foals, pre-colostral serum normally contains no or only very small quantities of γ-globulins, but within a few hours after the intake of colostrum, γ-globulins begin to rise in serum and the absorption continues for up to 36 h after birth, after which gut permeability ceases (Weaver et al 2000;Blum 2006). Hypogammaglobulinaemia may be commonly seen also in patients with recurrent infections or in cases of immune deficiency (Cunningham-Rundles…”
Section: Globulinsmentioning
confidence: 99%